Contemporary posterior surgical approach in total hip replacement: still more reoperations due to dislocation compared with direct lateral approach? An observational study of the Swedish Hip Arthroplasty Register including 156, 979 hips. (3rd September 2019) - Skoogh, Oscar; Tsikandylakis, Georgios; Mohaddes, Maziar; Nemes, Szilard; Odin, Daniel; Grant, Peter; Rolfson, Ola
Abstract : Background and purpose — The direct lateral approach (DLA) and the posterior approach (PA) are the most common surgical approaches in total hip replacement (THR) in Sweden. We investigated how the relationship between surgical approach and risk of reoperation due to dislocation has evolved over time. Patients and methods — Data were extracted from the Swedish Hip Arthroplasty Register from 1999 to 2014. We selected all THRs due to osteoarthritis with head sizes 28, 32, and 36 mm that were performed with either the DLA or the PA. Resurfacing prostheses were excluded. Kaplan–Meier curves for risk of reoperation due to dislocation and all-cause for the 2 surgical approaches were compared for 2 periods (1999–2006 and 2007–2014) up to 2 years postoperatively. We used Cox regression for sex, age, type of fixation, and head size to determine hazard ratios (HR) with DLA set as reference. Results — 156, 979 THRs met the selection criteria. In 1999–2006, the PA was associated with increased risk of reoperation due to dislocation (HR 2.3, 95% CI 1.7–3.0) but there was no difference in the risk of all-cause reoperation (HR 1.1, CI 0.9–1.2). In 2007–2014 there was no statistically significant difference in the risk of reoperation due to dislocation (HR 1.2, CI 0.9–1.6) but the risk of all-cause reoperation was lower (HR 0.8, CI 0.7–0.9) for the PA. Interpretation — This study confirms historic reports on the increased risk of early reoperations due to dislocations using the PA compared with the DLA. However, in contemporary practice, the higher risk of reoperation due to dislocation associated with PA has declined, now being similar to that after DLA. We believe improved surgical technique for the PA may explain the results. Surprisingly, the PA was associated with lower risk of all-cause reoperation in 2007–2014. This finding warrants further investigation.